Identification of Four Distinct Phylogenetic Groups in Flavobacterium columnare With Fish Host Associations - LaFrentz, Benjamin R.; García, Julio C.; Waldbieser, Geoffrey C.; Evenhuis, Jason P.; Loch, Thomas P.; Liles, Mark R.; Wong, Fong S.; Chang, Siow F. (Frontiers in Microbiology, 2018)
Columnaris disease, caused by the Gram-negative bacterium Flavobacterium columnare, is one of the most prevalent fish diseases worldwide. An exceptionally high level of genetic diversity among isolates of F. columnare has long been recognized, whereby six established genomovars have been described to date. However, little has been done to quantify or characterize this diversity further in a systematic fashion. The objective of this research was to perform phylogenetic analyses of 16S rRNA and housekeeping gene sequences to decipher the genetic diversity of F. columnare. Fifty isolates and/or genomes of F. columnare, originating from diverse years, geographic locations, fish hosts, and representative of the six genomovars were analyzed in this study. A multilocus phylogenetic analysis (MLPA) of the 16S rRNA and six housekeeping genes supported four distinct F. columnare genetic groups. There were associations between genomovar and genetic group, but these relationships were imperfect indicating that genomovar assignment does not accurately reflect F. columnare genetic diversity. To expand the dataset, an additional 90 16S rRNA gene sequences were retrieved from GenBank and a phylogenetic analysis of this larger dataset also supported the establishment of four genetic groups. Examination of isolate historical data indicated biological relevance to the identified genetic diversity, with some genetic groups isolated preferentially from specific fish species or families. It is proposed that F. columnare isolates be assigned to the four genetic groups defined in this study rather than genomovar in order to facilitate a standard nomenclature across the scientific community. An increased understanding of which genetic groups are most prevalent in different regions and/or aquaculture industries may allow for the development of improved targeted control and treatment measures for columnaris disease.